Reconstructing Social Fiqh in Contemporary Islamic Finance: A Maqashid Analysis of DSN-MUI Fatwa on Sukuk-Waqf - Nurlaili Adkhi Rizfa Faiza; Ita Marianingsih Purnasari; Hafidhotul Amaliyah; Muhammad Lathoif Ghozali (Share: Jurnal Ekonomi dan Keuangan Islam, 2026)
The development of contemporary Islamic finance requires the innovation of instruments that are not only compliant with sharia but also inclusive, sustainable, and aligned with the principles of maqāṣid al-sharīʿa to address modern socio-economic challenges. This study aims to examine DSN-MUI Fatwa No. 131/2019 on sukuk waqf as a manifestation of progressive social fiqh within the architecture of modern Islamic finance, particularly in articulating and operationalizing maqāṣid objectives. A qualitative-descriptive method with a normative approach is employed, utilizing document analysis of the fatwa and interpreting it through the maqāṣid frameworks of Abu Zahrah and Abdul Majid al-Najjar. The findings indicate that sukuk waqf represents a hybrid financial instrument that integrates the philanthropic nature of waqf with the structured mechanisms of Islamic capital markets, while reflecting key maqāṣid dimensions such as individual development, justice, social cohesion, and environmental sustainability. Furthermore, the fatwa demonstrates the role of DSN-MUI as an institutional ijtihād authority capable of synthesizing classical jurisprudence with contemporary financial needs. These findings imply that maqāṣid al-sharīʿa serves as a critical normative framework for designing and evaluating Islamic financial instruments that are value-oriented and socially responsive, while also highlighting the potential for broader application of sukuk waqf across various socio-economic sectors. ABSTRAK - Rekonstruksi Fiqh Sosial dalam Keuangan Islam Kontemporer: Analisis Maqashid atas Fatwa DSN-MUI tentang Sukuk Wakaf. Perkembangan keuangan Islam kontemporer menuntut inovasi instrumen yang tidak hanya sesuai dengan prinsip syariah, tetapi juga inklusif, berkelanjutan, dan berorientasi pada maqashid al-sharia guna menjawab tantangan sosial-ekonomi modern. Penelitian ini bertujuan untuk menganalisis Fatwa DSN-MUI No. 131/2019 tentang sukuk wakaf sebagai manifestasi fiqh sosial progresif dalam arsitektur keuangan Islam modern, khususnya dalam merepresentasikan dan mengoperasionalkan tujuan-tujuan maqashid. Penelitian ini menggunakan metode kualitatif-deskriptif dengan pendekatan normatif melalui analisis dokumen fatwa serta interpretasi menggunakan kerangka maqashid Abu Zahrah dan Abdul Majid al-Najjar. Hasil penelitian menunjukkan bahwa sukuk wakaf merupakan instrumen keuangan hibrida yang mengintegrasikan karakter filantropi wakaf dengan mekanisme terstruktur pasar modal syariah, sekaligus mencerminkan dimensi utama maqashid seperti pembinaan individu, keadilan, kohesi sosial, dan keberlanjutan lingkungan. Selain itu, fatwa ini menegaskan peran DSN-MUI sebagai lembaga ijtihad kelembagaan yang mampu mensinergikan warisan fiqh klasik dengan kebutuhan keuangan kontemporer. Temuan ini mengimplikasikan bahwa maqashid al-sharia berfungsi sebagai kerangka normatif penting dalam perancangan dan evaluasi instrumen keuangan Islam yang berorientasi pada nilai dan kemaslahatan, serta membuka peluang pengembangan sukuk wakaf di berbagai sektor sosial-ekonomi.